Strategi Pengembangan Motivasi Berwirausaha Melalui Mata Kuliah Kewirausahaan Pada Mahasiswa FISIP Universitas Negeri Semarang - Puspita, Maharani Intan; Nurul Fatimah (Universitas Negeri Semarang, 2025)
Entrepreneurship is the ability to create new innovations that have value in order to achieve a goal in conducting business activities. In conducting entrepreneurial activities, motivation is important for each individual to achieve success in doing business. The purpose of this research was to find out what strategies were given and the impact of giving these strategies to increase motivation in entrepreneurial activities through entrepreneurship courses for students, especially the Faculty of Social and Political Sciences, Semarang State University. The approach used in this research is a qualitative approach, while the data collection technique uses mixed methods. The qualitative data of this research was obtained through observation, interview, literature study, and the quantitative data was obtained from distributing questionnaires through google form. The theory used in this study is the theory of achievement needs put forward by McClelland relating to entrepreneurial motivation. The results found from this study are three strategies, namely, the provision of compulsory entrepreneurship courses, entrepreneurship expo activities, and entrepreneurship seminars. While the impact caused is the emergence of enthusiasm, innovative, creative, and artistry in taking risks. With the implementation of these three strategies as well as the collaboration between educational institutions and students, student entrepreneurial motivation will certainly be formed.